AS IMPLICAÇÕES DA BNC-FORMAÇÃO PARA A FORMAÇÃO DOCENTE: CONSIDERAÇÕES A PARTIR DA PERSPECTIVA CRÍTICA. - Nayla Marcatto da Costa (2023)
In the current context of Brazilian education, we see how political and motivated issues are the initial training of teachers. We noticed that the National Curriculum Guidelines (DCN) protect a setback as a consequence of the approval of Resolution n. 02/2019, as they are based on theories that favor the skills and abilities contained in the National Common Curricular Base (BNCC), rather than theories that focus on the development of the teachers' conceptual thinking. Thus, we have the following problems: What are the BNC-training instructions for teacher training, from a critical perspective. The main objective is to analyze the DCN of 2015 and 2019 to understand how they condition teacher training. This research was carried out based on dialectical historical materialism. The main references used are Vygotsky (1930, 1995, 2001, 2010, 2018), Leontiev (1978, 2004), Marx (2004, 2013), Saviani (1996, 1999, 2009, 2011, 2019), Libâneo (2005). The method used was Bibliographic and Documentary Research, with an ontological approach. The analysis is based on the theoretical critique of the guideline concepts in comparison with the theoretical analysis in the critical perspective. We understand in a theoretical-critical way how English for the initial training of teachers, from the concepts Education, School Education, Curriculum, Praxis/Practice, Training and Teaching Work and Competence, found in the documents already mentioned and in the studies of critical approach. The main result refers to the analysis that the DCN of 2019 present a setback due to the focus on preparing the student for the job market, through the competences imposed on teacher training based on the BNC-Training, disregarding human training of the individual from the perspective of the Historical-Cultural Theory.